PERANAN KEPALA SEKOLAH DALAM MENGEMBANGKAN SIKAP CIVIC RESPONSIBILITY TERHADAP DISIPLIN GURU - Lina Marlina; Restiana Restiana (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2019)
This research is motivated by teacher discipline problem that is: some teachers are less timely present in school and enter class, teacher leave class while lesson still ongoing teacher just give task record and problem to student so that student is outside class and outside school during class time take place. The purpose of this research is to know the role of principal in developing civic responsibility attitude toward teacher discipline (Descriptive Study at SMA Negeri 1 Padarincang Class XI IPS1) and to know principal technique in developing civic responsibility attitude to monitor teacher discipline (Descriptive Study at SMA Negeri 1 Padarincang Kelas XI IPS1). The method of this research is descriptive with the depiction in fact, the data in the form of language expression and discourse is appropriate and systematic, qualitative research is a research used to examine the condition of the object that Scientific, where Researcher is as a key instrument. The results of this study indicate the role and responsibilities of principals to support teachers in improving teacher competence, supervision techniques performed by the principal is good at providing examples of discipline against teachers. The conclusion of this research the principal reminded teachers of every ceremony on Monday and meetings to salary and idolize the first day of each week, the principal conducts X-XII class visits, checks the teacher's teaching program such as syllabus, RPP, checks the X-XII class agenda and fix the layout of the room in the school. Suggestions in this study teachers are expected to be on time attend school and enter the classroom, the teacher does not leave the class during the lesson so that students are not outside the classroom or outside the school.